A Systematic Literature Review Exploring Achievement Outcomes and Therapeutic Factors for Group Counseling Interventions in Schools. Issue 1 (14th March 2022) - Steen, Sam; Melfie, Jennifer; Carro, Annie; Shi, Qi
This article presents a systematic review of group counseling interventions facilitated by school counselors that included academic achievement as outcome targets. We examined the articles that met the criteria to identify any therapeutic factors within the group interventions. A total of 18 articles met the criteria and all of the studies with the largest effect size (i.e., above .8) were found to have imparting information as one of the therapeutic factors coded as part of the intervention. Five articles were either qualitative in nature or did not present enough descriptive data to calculate effect size. These articles included at least three therapeutic factors and raised an important implication for mixed-method research studies to ensure more inclusive approaches in the future. We provide recommendations for practice and research and conclude this article with a call for more group counseling research in schools.